(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
This study aims to illustrate the rise and the early developments of the epigraphic culture in Magna Graecia. It will pay special attention to the social roots, aspects and implications of these two highly complex phenomena, which are involved in the wider events of the rise and the early evolution of the Greek alphabet. For this purpose, the work will take into examination some meaningful documents, in order to highlight, occasions, contexts, means, ways and practices related to the use of writing.